2019
DOI: 10.3390/jmse7050144
|View full text |Cite
|
Sign up to set email alerts
|

Geomorphological Processes and Environmental Interpretation at Espalmador islet (Western Mediterranean)

Abstract: This study presents a sedimentological and stratigraphical description of the Pleistocene deposits cropping out in Espalmador islet (Illes Pitiüses). Four major sedimentary facies including the succession of aeolian, marine, colluvial and edaphic environments are described. The sedimentological and stratigraphical analysis of these deposits allows the reconstruction of the coastal Pleistocene environmental and geomorphological history of the Espalmador islet. The coastal relief and the fluctuations of the sea … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…However, when the region is located in the same climate type, the influence of climate on the spatial pattern of vegetation differentiation is small, and the influence of topography and geomorphology on the distribution of vegetation is obvious. Geomorphological processes interfere with surface soil erosion, landslides, and collapses, disturbing the living environment and growth area of vegetation [53][54][55]. At the same time, soil is transported to the lower slopes of hills through accumulation.…”
Section: Study Of the Influence Of Geomorphic Spatial Differentiation...mentioning
confidence: 99%
“…However, when the region is located in the same climate type, the influence of climate on the spatial pattern of vegetation differentiation is small, and the influence of topography and geomorphology on the distribution of vegetation is obvious. Geomorphological processes interfere with surface soil erosion, landslides, and collapses, disturbing the living environment and growth area of vegetation [53][54][55]. At the same time, soil is transported to the lower slopes of hills through accumulation.…”
Section: Study Of the Influence Of Geomorphic Spatial Differentiation...mentioning
confidence: 99%
“…Several studies have used dating methods to establish the time framework of aeolianites and beachrock formation and to assess their connection with sea level changes [50][51][52][53]. Aeolianites are mainly considered to be deposited around the world at sea level high stands [54,55], but several recent studies have indicated the cold and low sea level scenario as a genetic mechanism for the formation and accumulation aeolian deposits [56][57][58][59][60][61][62][63]. Differences in the timing of deposition and morphology of aeolian dunes during major sea level changes (high stands, low stands) among regions appear to be dependent on the interactions caused by minor-secondary sea level changes, local climatic conditions, sediment availability, and differences in the inland-near-shore topography [64].…”
Section: Beachrocks and Aeolian Depositsmentioning
confidence: 99%
“…Several studies have used dating methods to establish the time framework of aeolianites and beachrock formation and assess their connection with sea level changes [64][65][66][67]. Aeolianites are mainly considered to be deposited around the world at sea level high stands [68,69], but there are several recent studies indicate as a genetic mechanism for the formation and accumulation aeolian deposits the cold and low sea level scenario [70][71][72][73][74][75][76][77]. Differences in the timing of deposition and morphology of aeolian dunes during major sea level changes (high stands, low stands) among regions appear to be dependent on the interactions caused by minor-secondary sea level changes, local climatic conditions, sediment availability, and differences in the inland-near-shore topography [78].…”
Section: Introductionmentioning
confidence: 99%